2019
DOI: 10.33175/mtr.2019.140730
|View full text |Cite
|
Sign up to set email alerts
|

A review of unmanned surface vehicle development

Abstract: This paper provides a review on development of unmanned surface vehicles (USVs). Their potential applications and development trends are also discussed. Based on active works in this fields, USVs may potentially be integrated into existing force structures of manned ships, offering a cost-effective solution for performing various types of marine operations with a minimum risk on the personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…A great number of ASVs with different capabilities and functionalities was developed, mostly in the last twenty years, arising from academic and research institutions [ 8 ]. The current literature provides detailed ASV’s state of the art like [ 9 , 10 ] or, more recently, [ 11 , 12 ]. Regarding research and development, several relevant projects have been reported, carrying out different operations in aquatic scenarios like in [ 13 , 14 , 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…A great number of ASVs with different capabilities and functionalities was developed, mostly in the last twenty years, arising from academic and research institutions [ 8 ]. The current literature provides detailed ASV’s state of the art like [ 9 , 10 ] or, more recently, [ 11 , 12 ]. Regarding research and development, several relevant projects have been reported, carrying out different operations in aquatic scenarios like in [ 13 , 14 , 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…Unmanned Surface Vehicles, USV) olmak üzere üç alt türde ele alınmaktadır (Tanakitkorn, 2019). Çalışmamızın konusu olan insansız gemileri de kapsayan İSA'lar insansız işletime izin veren deniz taşıtlarıdır ve uzaktan kumandayla işletilebildiği gibi, asgari insan müdahalesiyle kendi kararlarını kendi veren otonom araçlar olarak da işleyebilmektedir (Tanakitkorn, 2019). Deketelaere (2017) insansız gemileri, A noktasından B noktasına üzerindeki personelden destek almadan seyredebilen gemi olarak tanımlamıştır.…”
Section: İnsansız Araçların Sınıflandırılmasıunclassified
“…Misalnya, USV dapat dilengkapi dengan sistem sonar untuk mencari dan mencegah kemungkinan ancaman bawah laut di wilayah strategis. Penggandaan gaya ini juga sangat berguna untuk penelitian kelautan skala besar; misalnya, penggunaannya untuk survey lingkungan [5] Dimensi lambung kapal memiliki panjang = 1000 mm, lebar = 400 mm, dan tinggi = 200 mm.…”
Section: Pendahuluanunclassified